Perancangan Ulang Museum Pendidikan Upi Bandung - Santa Wardani, Oktiprima; Liritantri, Widyanesti; Retno Palupi, Fajarsani (Telkom University, 2024)
Indonesia there are many museums, one of which is the UPI National Education Museum which is located in the Bandung Indonesian University of Education area. This museum has a collection that focuses on education which is presented in the form of books, equipment used from classical times to modern times, written information, statues, and dioramas depicting educational events. In the arrangement of existing collections, the interior of the UPI National Education Museum, most of the rooms have a lighting design that does not meet the needs of an exhibition space which should be able to display colors, shapes, textures, and information clearly to enable visitors to see the collection objects and texts clearly and with information. well accepted. The design exploration study will show the design process for lighting and arranging collection displays using an architectural lighting design approach. This study uses a practice-based research method, where exploration includes real activities as a visitor as part of the data search process. The results of the exploration show alternative lighting that is able to create an attractive space ambiance and is in line with the museum's objectives, namely clearly displaying information from collection objects and the texts presented. The contribution of this design can provide new insights for museums to create good and innovative lighting. Keywords: museum, education, lighting